Frailty is an independent determinant of COVID-19 vaccine hesitancy in the elderly: a cross-sectional study: Frailty is a determinant of COVID-19 vaccine hesitancy - Xiong, Lu; Han, Mei; Wang, Chunmiao; Liu, Kai; Liu, Tao (Cellular and Molecular Biology, 2022)
COVID-19 vaccines have become an important hope for slowing down or stopping the pandemic. As the population ages, older adults will comprise a greater proportion of the vaccinated population. We aimed to assess influencing factors of COVID-19 vaccine hesitancy in older adults. For this aim, We conducted a cross-sectional study on a questionnaire survey of the elderly over 65 years living in the community of Haikou City from August 1st to September 30th, 2021. Univariate and multivariate Logistic regression analyses were performed to identify factors related to vaccine hesitancy. We analyzed completed questionnaires from 225 respondents (42.2% women, mean age 73.4±6.2 years). There were 99 people in the vaccine hesitation group and 126 people in the vaccine acceptance group, the incidence of vaccine hesitation in the elderly population is about44%（99/225）. The incidence of frailty in the vaccine hesitation group was much higher than that in the vaccine trust group (62.63 vs. 30.95%, P＜0.001). The risk factors of vaccine hesitancy in the elderly aged 70-75years and over 75 years were 2.987 times and 3.587 times higher than that in the population aged 65-70 years (OR=2.987,95%CI: 1.424-6.265, P＜0.001; OR=3.587,95% CI:1.804-7.131, P＜0.001). Frailty is also an independent risk factor of vaccine hesitancy in the elderly population (OR=2.624,95%CI: 1.447-4.757, P＜0.001). Then the vaccination rate of the COVID-19 vaccine is far from reaching the requirements of herd immunity, and more flexible and comprehensive efforts are needed to increase the vaccination willingness of the frail elderly.